Assessing the Tri-Dimensional Nexus of Energy, Environment, and Economic Growth in Pakistan: An Empirical Study - Muhammad, Fida; Qayyum, Abdul; Bawazir, Abdullah Abdulaziz; Jan, Meer; Ahmed, Nazeer (International Journal of Energy Economics and Policy, 2024)
The energy sector plays a crucial role in boosting economic growth and improving the standard of living in Pakistan. However, the extensive use of energy from different sources, such as hydel, nuclear, and thermal energy, has resulted in significant impacts on environmental degradation and negative health impacts for local communities. The study examined the tri-dimensional nexus between different types of energy use, economic growth, and environmental degradation in Pakistan using the ARDL regression model with data spanning from 1972 to 2021. The empirical findings show that overall energy consumption, including hydro, nuclear, and thermal energy, has a positive and significant impact on economic growth in both the short and long term. This suggests that energy consumption is the main driver of economic growth, emphasizing the need for a sufficient supply of energy to meet the economy’s needs. On the environmental front, the study lends support to the existence of the EKC hypothesis in the context of Pakistan. However, in the long run, biocapacity in terms of forest products has a positive effect, whereas hydro, nuclear, and thermal energy have a negative effect on environmental quality. But in the short run, nuclear and hydroelectric energy have a positive but insignificant effect on ecological footprints. These findings suggest the need for Pakistan to focus on reducing the use non-renewable energy and promoting the use of cleaner energy sources to mitigate environmental impacts. This study also highlights the importance of policymakers considering the environmental consequences of energy and growth when making decisions in Pakistan.